Density functional theory-based modeling and calculations of a polyamide molecular unit for studying forward-osmosis-dewatering of microalgae - Itliong, Jester N. (Animo Repository, 2019)
Both the preparation of a reliable all-atom model of a polyamide (PA) membrane and the determination of its electrostatic parameters are considered significant challenges in a proposal to study forward-osmosis-dewatering of microalgae using molecular dynamics (MD). Density functional theory (DFT)-based calculations can effectively calculate for optimized structure and electrostatic properties, thus, employed to model and characterize the PA membrane starting from its molecular unit. The performed structural optimization resulted to the most stable configuration of the PA unit with bond length values that showed strong stability in the molecule such as the amide bond length of 1.413 Å which was found to differ from that of a related study by 3%. The calculated charge density distributions, electrostatic potential isosurface, and Mulliken charges on the PA unit provided potential binding sites and insights on the formation of amide bonds on the PA molecule. The non-amidebonded nitrogen atom of m-phenylene diamine (MPD) was found to be the most active site in the molecule due to its highest magnitude of negative charge (positive Coulomb potential), suggesting that amide bond-formation with a carbon atom of a trimesoyl chloride (TMC) monomer is most likely to occur during polymerization. The calculated charges in the amide group and the zero-net sum of these charges also agreed reasonably well with another study. The results are of vital importance in parameterizing the interaction potentials of PA for use in the MD simulations. © 2018 IEEE.